Near-Ir Observations of the Young Star [Bhb2007]-1: A Substellar Companion Opening the Gap in the Disk - Perez-Marquez, S (IOP Publishing Ltd, 2021)
The presence of planets or substellar objects still embedded in their native protoplanetary disks is indirectly suggested by disk substructures like gaps, cavities, and spirals. However, these companions are rarely detected. We present Very Large Telescope/NACO high-contrast images in the J, H, K S , and L ′ bands of the young star [BHB2007]-1 probing the inclined disk in scattered light and revealing the probable presence of a companion. The point source is detected in the L ′ band in spatial correspondence with complementary Very Large Array observations. This object is constrained to have a mass in the range of 37-47 M Jup and is located at 50 au from the central star, inside the 70 au-large disk cavity recently imaged by the Atacama Large Millimeter/submillimeter Array (ALMA), that is absent from our NACO data (down to 20 au). This mass range is compatible with the upper end derived from the size of the ALMA cavity. The NIR disk brightness is highly asymmetric around the minor axis, with the southern side 5.5 times brighter than the northern side. The constant amount of asymmetry across all wavelengths suggests that it is due to a shadow cast by a misaligned inner disk. The massive companion that we detect could, in principle, explain the possible disk misalignment, as well as the different cavity sizes inferred by the NACO and ALMA observations. The confirmation and characterization of the companion is entrusted to future observations. © 2021. The American Astronomical Society. All rights reserved..